DEAGRICHAIN Blockchain-based solution for agriculture - Pateil, Sachine; Kumbhar, Omkar Ashok; Jedhe, Sanchita Kuldeep; Palve, Payal Shahadeo; Mali, Shubham Mahavir (Journal of Trends in Computer Science and Smart Technology, 2023)
This research aims to develop a decentralized application (Dapp) for food supply chain traceability using blockchain technology. The Dapp enables consumers to track the journey of their food from the farm to their table, providing transparency and accountability to the supply chain. The Dapp is built on a blockchain platform using smart contracts to record and verify transactions between various stakeholders in the supply chain, including farmers, distributors, retailers, and consumers. Each stakeholder will have a unique identifier on the blockchain, and all transactions will be recorded in a tamper-proof and immutable manner. This work will contribute to the development of a more sustainable and trustworthy food supply chain, promoting ethical and environmentally friendly production practices. The Dapp will also provide opportunities for small-scale farmers and local producers to access larger markets and improve their profitability. Overall, this Dapp will help to create a more efficient, transparent, and accountable supply chain, benefiting all stakeholders, including suppliers, manufacturers, distributors, retailers, and consumers.